Complicated lives: girls, parents, drugs, and juvenile justice - Lopez, Vera (The Rutgers series in childhood studies, 2017)
Introduction -- Growing up in a "dysfunctional" family -- Mothers' little helpers -- Daddy's little girl: feeling rejected, abandoned, and unloved -- Looking for love in all the wrong places -- Doing drugs: the good, the bad, and the ugly -- Parents' attempts to intervene on behalf of drug-using daughters -- Property of the state: locked up, locked out, and in need of treatment -- Moving beyond the individual toward programmatic, systemic, and policy solutions